Prognostic prediction by hypermetabolism varies depending on the nutritional status in early amyotrophic lateral sclerosis - Ryutaro Nakamura (Nature Portfolio, 2021)
Abstract To examine whether hypermetabolism could predict the prognosis of early amyotrophic lateral sclerosis (ALS) patients with differing nutritional profiles. This single-center, retrospective study examined the prognosis of ALS patients with hypermetabolism in relation to their nutritional status at hospitalization. The metabolic state was estimated by the ratio of measured resting energy expenditure (mREE) to lean soft tissue mass (LSTM) (mREE/LSTM), wherein patients with ratios ≥ 38 were defined as hypermetabolic. Malnutrition was defined as %ideal body weight < 0.9. Forty-eight patients were enrolled in this study. The hypermetabolic group had shorter survival in the normal-weight group but more prolonged survival in the malnutrition group. Multiplication of nutritional and metabolic factors, such as [(body mass index (BMI) − 19.8) × (mREE/LSTM − 38)], designated as BMI-muscle metabolism index (BMM index), successfully predicted the prognosis in the group with a high BMM index (≥ 1), which showed shorter survival and a faster rate of weight loss and functional decline. Multivariate analysis using the Cox model showed high BMM index was an independent poor prognostic factor (hazard ratio: 4.05; p = 0.025). Prognostic prediction by hypermetabolism varies depending on the nutritional status in ALS, and the BMM index is a consistent prognostic factor.